2014
DOI: 10.1126/scitranslmed.3008089
|View full text |Cite
|
Sign up to set email alerts
|

Targeting miR-21 to Treat Psoriasis

Abstract: Psoriasis is a common inflammatory skin disease with limited treatment options that is characterized by a complex interplay between keratinocytes, immune cells, and inflammatory mediators. MicroRNAs (miRNAs) are regulators of gene expression and play critical roles in many human diseases. A number of miRNAs have been described to be up-regulated in psoriasis, but their causal contribution to disease development has not been demonstrated. We confirm that miR-21 expression is increased in epidermal lesions of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
136
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(140 citation statements)
references
References 32 publications
4
136
0
Order By: Relevance
“…Since TACE mRNA levels were not elevated in K5.Stat3C mice, this finding suggested that Stat3 signaling contributed to enhanced TACE activity via post-transcriptional regulation. Most recently, it has been reported that microRNA-21 (miR-21) targeted TIMP-3 and was functionally involved in the pathogenesis of psoriasis [51]. Most interestingly, miR-21 expression was up-regulated by the Stat3 signaling [52], supporting our data using K5.Stat3C keratinocytes, which showed acute decline of TIMP-3 upon TPA treatment, thereby TACE activity might be elevated, followed by release of the TACE substrates.…”
Section: Discussionsupporting
confidence: 87%
“…Since TACE mRNA levels were not elevated in K5.Stat3C mice, this finding suggested that Stat3 signaling contributed to enhanced TACE activity via post-transcriptional regulation. Most recently, it has been reported that microRNA-21 (miR-21) targeted TIMP-3 and was functionally involved in the pathogenesis of psoriasis [51]. Most interestingly, miR-21 expression was up-regulated by the Stat3 signaling [52], supporting our data using K5.Stat3C keratinocytes, which showed acute decline of TIMP-3 upon TPA treatment, thereby TACE activity might be elevated, followed by release of the TACE substrates.…”
Section: Discussionsupporting
confidence: 87%
“…ROS‐mediated apoptosis induction in AML (THP‐1) is low due to defects in p38‐dependent downstream signaling, and we here strived to further decipher the redox signaling that possibly contribute to this resistance in order to find new targets for AML treatment. Several reports demonstrated that AP‐1 factors in both, the innate (THP‐1) and the adaptive immune system (Jurkat) have important roles in human diseases and cancer . AP‐1 subunits, such as JUN, JUND, and FOS, are important for cell fate decisions, and their phosphorylation is often regulated by mitogen‐activated (MAP) kinases, for example, Jnk and p38 .…”
Section: Resultsmentioning
confidence: 99%
“…Guinea-Viniefar et al demonstrated that the inhibition of miR-21 ameliorated disease pathology in patient-derived psoriatic skin xenotransplants in mice and in a psoriasis-like mouse model [34]. Zhao et al reported that the down-regulation of miR-210 improves immune dysfunction in CD4 + T cells of psoriasis patients [35].…”
Section: Discussionmentioning
confidence: 97%